Notas sobre la biología y el manejo en laboratorio del acaro depredador Amblyseius victoriensis (Womersley) (Acari: Phytoseiidae) - Ruíz Cancino, Enrique; Blanco, Juana María; Máteos Crespo, Juan R. (Instituto de Ecología, A.C., 1999)
The introduction of Amblyseius victoriensis from Australia to Tamaulipas, México, for laboratory studies, is recorded. Notes on the biology of this predator of Eriophyidae pest mites, and pollen, prey, and predator management are given.